Effect of different levels of Citrus sinensis peel extract on broiler performance, blood parameters, thyroid gland activity and bone ash - SEIDAVI, ALIREZA; EBRAHIMI, ABBAS; ALAW QOTBI, ALI AHMAD; NIETO, JOSE ÁNGEL GÓMEZ (The Indian Journal of Animal Sciences, 2015)
A 6-week experiment involving 400 day-old Ross 308 chicks was carried out in a completed randomized design to evaluate the performance, thyroid gland activity, haematological parameters and bone ash of the broilers supplemented with Citrus sinensis peel extract (CSPE) in drinking water. The birds were allotted to 5 treatments containing basal diet (control), basal diet supplemented with 1000 ppm in drinking water for 1 to 21 days, 1000 ppm for 1 to 42 days, 1250 ppm for 1 to 21 days or 1250 ppm for 1 to 42 days. Each treatment was replicated four times, 20 chicks each. Results showed that the addition of CSPE in drinking water, irrespective of its concentration or the growth period when it is added, improves weight gain and feed conversion ratio in the 22 to 42 days of growth period. Red blood cells counts were higher for the four treatment groups compared to the control one and packed cell volume were higher for both groups added with 1250 ppm CSPE but no differences between treatment groups and control one were found in plasma T3 and T4 concentrations, Hg concentration or bone ash. So, the authors can conclude that the addition of orange could be positive for the poultry industry as well as a cheap substitute for the traditional antibiotics.